Letter - Morgan, Betty
038-0057-001 Mr. Parkin BASQUE CHILDREN'S COMMITTEE CHAIRMAN: THE DUCHESS OF ATHOLL, D.B.E., D.C.L. VICE-CHAIRMEN: MISS ELEANOR RATHBONE, M.P. H.V. TEWSON, ESQ. HON. SECRETARIES: Mr. WILFRID ROBERTS, ESQ. M.P. LT.-COL. J.R.J. MACNAMARA, M.P. Mr. D.R. GRENFELL, M.P. HON. TREASURER: VISCOUNT CECIL OF CHELWOOD, P.C. K.C. ORGANISING SECRETARY: DR. BETTY MORGAN. 30, ECCLESTON STREET, LONDON, S.W.1. TELEPHONE: SLOANE 9866 Your Ref. HVT/FC/233. December 21st, 1939. H.V. Tewson, Esq., Trades Union Congress, Transport House, Smith Square, London, S.W.1. Dear Mr. Tewson, On behalf of the Basque Children's Committee, may I ask you to express to the Trades Union Congress our most sincere thanks for the generous gift of £300 as a grant towards the repatriation expenses of the Basque children. Your cheque comes at a most opportune time when we are struggling to raise every possible penny for the support of the 500 Basque children who must remain in this country because their parents are refugees in France or prisoners in Spain. Yours sincerely, Betty Morgan Organising Secretary. 292/946/38/57